The Implementation of the Cascading Method in Post-COVID-19 English Language Learning at SDN 3 Timpag Tabanan - Utik Kuntariati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This study examines the implementation of the Cascading learning model at SDN 3 Timpag, Kabupaten Tabanan, particularly in the context of students transitioning from online to offline learning due to COVID-19. The research employs a qualitative approach, using literary studies and document analysis to explore the current phenomenon and collect relevant data. The Cascading learning model is structured in five stages: (1) formulating cascading materials, (2) orientation, (3) grouping, (4) determination of materials and presentation, and (5) evaluation. These stages are crucial in developing the learning system, particularly for shaping students’ understanding of tourism objects integrated into English language learning materials. A SWOT analysis conducted in the study revealed key challenges: internally, some students have not fully adapted to the new learning model; externally, students experience learning loss, making it more difficult to develop creative thinking skills. Overall, the research emphasizes that the Cascading model can support the adjustment to offline learning while enhancing students’ engagement and creativity in English learning.